The spy who jumped off the screen - Caplan, Thomas (Viking, 2012)
Recruited on a clandestine mission to thwart the transfer of nuclear warheads into rogue hands, covert operative turned A-list movie star Ty Hunter uses all his skills as a spy, soldier, and actor to match wits with an enigmatic billionaire.